Quantitative Assessment of Environmental/Human Health Risks - Yan, Cheng (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the quantitative assessment of environmental and human health risks which are usually evaluated by the ecological risk assessment which is the process for evaluating how likely it is that the environment might be obstructed as a result of exposure to environmental stressors. This book can deliver novel data on the quantitative assessment framework and provide a theoretical basis for follow-up research on the mitigation measures and control strategies for stakeholders.